Getting Started with Microsoft Viva : an end user guide to business transformation - Hess, D'Arce (APress, 2022)
Use the power of analytics, knowledge management, and discovery for improved employee retention and insight to the unique collaborative and learning needs of your organization using Viva, Microsoft's new employee experience platform. This book introduces you to the four central tenets of Microsoft Viva, a platform designed to improve communication, knowledge, learning, and insight within an organization. The authors, all Microsoft MVPs and early users of Viva, share their first-hand experiences and knowledge to teach you how to configure, utilize, and adopt Viva Topics, Viva Connections, Viva Learning, and Viva Insights to drive knowledge management and discovery within an organization. In Part I, you will learn how to classify data and topics within your organization, and learn how the use of AI can bring to life the discovery of knowledge and information related to people and other topics, allowing for better understanding and clarity of the content you see every day. In Part II, you will learn how to bring the power of SharePoint Syntex and Viva Topics into Microsoft Teams. In Part III, you will learn how to build a shared learning portal in Microsoft Teams using your own training materials, or bringing in third-party resources such as LinkedIn Learning and Skillsoft to connect directly to your employees. Managers will appreciate the ability to assign learning topics to users and gain the skills needed to create a fundamental process around learning consolidation. In Part IV, you will be introduced to Viva Insights, and understand how to discover vital analytics for individuals, managers, and leaders. You will also learn how it supports your company's greatest asset, your employees. What You Will Learn Understand the basics of Viva to get up and running in no time Configure each vertical of Microsoft Viva Know the roles and pre-requisites for installation and configuration Organize and think about your content for discovery and relationships Deliver learning through an optimized experience for managers and users Leverage the power of SharePoint within Teams using Viva Connections Who This Book Is For Management, end users, and system administrators who want to step up their knowledge management, better train and retain employees, and improve access to internal content. The book is designed for businesses that want to transform the way they learn about content and people within their organization, with the end objective of making their business grow and thrive.